TRIB3 suppresses proliferation and invasion and promotes apoptosis of endometrial cancer cells by regulating the AKT signaling pathway - Qu, Junjie (Onco Targets Ther, 2019)
OBJECTIVE: The aim of this study was to examine the effect of TRIB3 on proliferation, apoptosis, and migration of endometrial cancer (EC) cells and explore the relationship between TRIB3 and AKT signaling pathway in EC progression. METHODS: Immunohistochemical analysis was performed to measure the expression level of TRIB3 in normal endometrium tissues and EC tissues. Overexpression and shRNA knockdown techniques were applied by transfecting EC cells (ISK and AN3CA), and the effect of TRIB3 on EC cell biological behaviors was evaluated. Cell Counting Kit-8 and colony formation assays were utilized to investigate EC cell proliferation ability, and flow cytometry was performed to assess the apoptosis of EC cells. Moreover, the migration and invasion of EC cells were detected by transwell assay, and the levels of MMP-2 and MMP-9 were measured by ELISA. Additionally, Western blot analysis was carried out to determine the levels of AKT and p-AKT. RESULTS: The expression level of TRIB3 was higher in EC than normal endometrium tissues, and its overexpression promoted apoptosis and suppressed proliferation of EC cells. Furthermore, TRIB3 retarded the migration and invasion of EC cells and decreased the levels of MMP-2 and MMP-9. Conversely, TRIB3 inhibition enhanced the expression levels of MMP-2 and MMP-9, and proliferation and migration of EC cells but suppressed their apoptosis. Similarly, TRIB3 overexpression reduced while its knockdown increased the level of p-AKT. CONCLUSION: TRIB3 inhibited proliferation and migration and promoted apoptosis of EC cells probably through regulating AKT signaling pathway.